2020
DOI: 10.3389/fpls.2020.554158
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Properties of Ultra-Late Maturing Peach Cultivars and Their Attributions to Melting Flesh (M) Locus: Re-evaluation of M Locus in Association With Flesh Texture

Abstract: The postharvest properties of two ultra-late maturing peach cultivars, “Tobihaku” (TH) and “Daijumitsuto” (DJ), were investigated. Fruit were harvested at commercial maturity and held at 25°C. TH exhibited the characteristics of normal melting flesh (MF) peach, including rapid fruit softening associated with appropriate level of endogenous ethylene production In contrast, DJ did not soften at all during 3 weeks experimental period even though considerable ethylene production was observed. Fruit of TH and DJ we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The fruit SSC and SSC/acid ratio of peach fruit were increased with advancing the storage period at 25 °C (Nuzzi, et al, 2015, Nakano et al, 2020, Shalan, 2020. In spite of that, Pinto et al (2015) found that the relationship between SSC and maturity indicators of peach fruit did not observe significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fruit SSC and SSC/acid ratio of peach fruit were increased with advancing the storage period at 25 °C (Nuzzi, et al, 2015, Nakano et al, 2020, Shalan, 2020. In spite of that, Pinto et al (2015) found that the relationship between SSC and maturity indicators of peach fruit did not observe significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Peaches less than 53 N firmness at harvest time will continue to ripen after harvest in good quality compared to those over 53 N firmness. While, peaches fruit in which firmness was 0.7 N/mm 2 at harvest, their firmness reduced dramatically to less than 0.2 N/mm 2 by day 7 at 25 °C (Nakano et al, 2020). However, peach fruit with firmness below 27 N are sensitive and able to be damaged during postharvest and handling.…”
Section: Introductionmentioning
confidence: 99%
“…Taking all of these results into consideration, we conclude that the two seeds were derived from the breakdown of SI in 'Sordum'. Japanese plum-specificity of the SNP genotype was confirmed using genomic sequencing data (Ono et al, 2018;Nakano et al, 2020;Numaguchi et al, 2019). Japanese apricot, apricot, peach, and sweet cherry were homozygous for "G", whereas Japanese plum was homozygous for "A" (data not shown).…”
Section: Genome Analysis To Confirm the Breakdown Of Simentioning
confidence: 96%
“…The first PCR analysis was conducted to exclude the possibility of interspecific hybridization with pollen from other Prunus species in the orchard where the experimental pollinations were conducted, as pollen grains from many Prunus species can readily grow in the pistils of Japanese plum (Morimoto et al, 2019). A Japanese plum-specific single nucleotide polymorphism (SNP) was identified in the early shoot regeneration (ESR) gene on chromosome 1 (data not shown) by mapping genomic DNA sequencing reads from four Japanese plum, 113 Japanese apricot, seven apricot (Numaguchi et al, 2019), three peach (Nakano et al, 2020), and seven sweet cherry cultivars (Ono et al, 2018). The Japanese plum-specificity of the SNP was further confirmed by sequencing the ESR gene of three Japanese plum, one Japanese apricot, one apricot, and two peach cultivars, and 'Stanley', the only European plum planted in the same orchard as described below.…”
Section: On-tree Si Evaluation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation